Foreign direct investment into crude oil exploitation and its impact on the economic growth and environment: Case study of Niger Delta oil producing communities / Salami Dada Kareem - Kareem, Salami Dada (2014)
In spite of the general perception of the debilitating impact of exploitation of crude oil on the economic growth and the environment of a country, from a conceptual viewpoint, evidence of lack of clarity on the solution to the problem of over-exploitation of crude oil in the Niger Delta region of Nigeria abounds. A body of research has consistently pointed out the numerous negative externalities brought to bear on the environment by the oil companies in the region. There is no consensus on the best way to solve the problem of externalities in the Nigerian oil industries. It is important to state that misappropriation of allocated resources, shifting market policy and institutional failure had characterized crude oil exploitation and had resulted in diverse economic and environmental problems. This study examines foreign direct investment in crude oil exploitation and its impact on economic growth and environment using the case study of the Niger Delta oil-producing communities. The methodology employed Quantitative technique such as structural equation modeling, co integration analysis and regression analysis to validate the propositions. The findings of the study showed that the path coefficients have higher value for environmental impact relative to that of well-being, which implied that the communities perceived that foreign direct investment into oil exploitation caused more destruction to their environment than the well-being of people. The basic model was extended to further examine the impact of foreign direct investment in the oil sector. Consistent with the basic model, it was found that foreign direct investment in the oil sector impacted more on the environment than on the well-being of the people. ii The results of the second proposition showed that a percentage increase in foreign direct investment in oil at lag 3 will increase Nigeria Gross Domestic Products by approximately 2 percent. The level of impact could be traced to foreign investors‟ influence and management of the oil and gas sector in Nigeria. The Nigerian economy has a high propensity to return on capital and needs lot more of domestic investment to influence its Gross Domestic Products. The trade openness seems to affect the economy adversely since trade liberalization impacted on Gross Domestic Products negatively. The study established that in Nigeria, natural resource endowment determines the level of economic activities and income generation capacity, but does not have any effect on the standard of living. Furthermore, the thesis also showed that the imposition of fines on the level of flared gas has no significant impact on reducing gas flaring; though it showed the potential to reduce gas flaring. In this wise, the Nigerian government needs to pursue strategies that will enhance effective competition between transnational corporations in the oil industry and indigenous companies without necessarily throwing them into experimental extinction. This should be complemented by persuading the multinationals to be committed to the social responsibilities to the host communities. In addition, government needs to emphasize the goal of achieving economic development through robust economic growth, poverty alleviation and unalloyed commitment to the protection of natural environment.